Is the Czech Republic a welfare state? - Christiana Kliková; Boris Navrátil (DANUBE: Law, Economics and Social Issues Review, 2019)
Is the Czech Republic a welfare state? This question is to be answered through this article, whose purpose is to classify Czechia into one of the types of the welfare state. The introduction of the article describes the creation of the welfare state and the main factors influencing its origin. The article also describes the characteristic features of the welfare state and presents its typology. The section entitled "The Czech Republic and the welfare state" expounds on the constituent stages of development of the Czech social policy until the present day. The article concludes with the comparison of some aggregate indicators and characteristics of social policies found in Sweden, Germany and the United Kingdom with similar indicators from the Czech Republic; this basis forms the assignment of the Czech Republic to one of the types of the welfare state.
Keywords: 330; Welfare State; Economic Policy; Social Policy; Public Social Services